Lithium titanate negative electrode material as well as preparation method and application thereof

By using two spray drying and two sintering methods in the preparation of lithium titanate negative electrode materials, the problem of low compaction density of lithium titanate negative electrode materials is solved, and the energy density of lithium ion batteries is improved.

CN119873881APending Publication Date: 2025-04-25GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821472.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The compaction density of lithium titanate negative electrode material is low, resulting in a lower energy density of lithium-ion batteries.

Method used

The preparation method of two spray drying and two sintering is adopted to limit the sintering temperature to 400-600°C to reduce the tightness of particle bonding and particle hardness, improve the particle size distribution width of particles, and enable small particles to fill the gaps between large particles, so as to achieve tight arrangement, thereby increasing the compaction density of lithium titanate negative electrode material.

Benefits of technology

By increasing the compaction density of lithium titanate negative electrode material, the energy density of lithium ion batteries is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873881A_ABST
    Figure CN119873881A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium titanate negative electrode material as well as a preparation method and application thereof, and relates to the technical field of secondary batteries. The preparation method of the lithium titanate negative electrode material comprises the following steps: S1, mixing a lithium source, a titanium source and a first solvent, and carrying out first ball milling treatment to obtain first slurry; s2, performing first spray drying treatment on the first slurry to obtain a first precursor; s3, performing first sintering treatment on the first precursor to obtain an intermediate product; s4, mixing the intermediate product with a second solvent, and carrying out second ball milling treatment to obtain second slurry; s5, performing second spray drying treatment on the second slurry to obtain a second precursor; and step S6, carrying out second sintering treatment on the second precursor to obtain the lithium titanate negative electrode material. Through the steps of twice spray drying, twice sintering and the like, the compaction density of the lithium titanate negative electrode material can be improved, and the improvement of the energy density of the battery is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium titanate negative electrode material and a preparation method and application thereof. Background Art

[0002] The negative electrode material of lithium-ion batteries is one of the main factors that affect the electrochemical performance of lithium-ion batteries. Among them, lithium titanate negative electrode materials have attracted widespread attention due to their good safety performance, long cycle life, stable charge and discharge platform, and excellent high and low temperature resistance. They can still work normally even in harsh environments of high temperature and extreme cold, and can be charged and discharged at high rates. However, the compaction density of lithium titanate negative electrode materials is low, resulting in a low energy density of the lithium titanate batteries formed by them, which is the main factor restricting the development of lithium titanate battery technology. Therefore, how to improve the compaction density of lithium titanate negative electrode materials, and then improve the energy density of lithium-ion batteries assembled therefrom, is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0003] The main purpose of the present invention is to provide a lithium titanate negative electrode material and a preparation method and application thereof, so as to solve the problem in the prior art that the compaction density of the lithium titanate negative electrode material is low, resulting in low energy density of lithium-ion batteries.

[0004] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a lithium titanate negative electrode material is provided, comprising the following steps:

[0005] Step S1, mixing a lithium source, a titanium source and a first solvent, and performing a first ball milling process to obtain a first slurry;

[0006] Step S2, subjecting the first slurry to a first spray drying process to obtain a first precursor;

[0007] Step S3, performing a first sintering treatment on the first precursor to obtain an intermediate product;

[0008] Step S4, mixing the intermediate product with a second solvent, and performing a second ball milling process to obtain a second slurry;

[0009] Step S5, subjecting the second slurry to a second spray drying process to obtain a second precursor;

[0010] Step S6, performing a second sintering treatment on the second precursor to obtain a lithium titanate negative electrode material;

[0011] The temperatures of the first sintering treatment and the second sintering treatment are independently 400 to 600°C.

[0012] Furthermore, the D50 particle size of the intermediate product is 200 nm to 1 μm.

[0013] Further, the first ball milling treatment is carried out at a rotation speed of 3000-4000 r / min for 1-3 h; and / or the second ball milling treatment is carried out at a rotation speed of 3000-4000 r / min for 1-3 h.

[0014] Furthermore, the temperature of the first spray drying process is 100 to 220°C, and the spray flow rate is 5 to 10 m 3 / h; and / or, the temperature of the second spray drying treatment is 100 to 220°C, and the spray flow rate is 5 to 10m 3 / h.

[0015] Furthermore, the first sintering treatment takes 1 to 3 hours, and the heating rate is 1 to 5°C / min; and / or the second sintering treatment takes 1 to 6 hours, and the heating rate is 1 to 5°C / min.

[0016] Furthermore, the molar ratio of lithium element to titanium element in the first slurry is 1:(1.20-1.25); and / or the lithium source includes at least one of lithium carbonate and lithium hydroxide; the titanium source includes at least one of titanium dioxide and titanic acid; and / or the first solvent and the second solvent are each independently selected from water; and / or the solid-liquid ratio in the first slurry is 10%-30%; and / or the solid-liquid ratio in the second slurry is 40%-80%.

[0017] The second aspect of the present invention provides a lithium titanate negative electrode material, which is prepared by the preparation method provided by the first aspect.

[0018] Furthermore, the lithium titanate negative electrode material is a secondary particle structure, and the secondary particles are composed of primary particles; the D50 particle size of the lithium titanate negative electrode material is 5 to 15 μm, the particle size distribution width is 2.5 to 2.8, and the specific surface area is 5 to 6 m 2 / g, tap density is 1.0~1.2g / cm 3 , compacted density is 2~2.5g / cm 3 .

[0019] The third aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator; wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and the material of the negative electrode active material layer comprises the lithium titanate negative electrode material provided in the second aspect.

[0020] Furthermore, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the material of the positive electrode active material layer includes one of a nickel cobalt manganese oxide material, a lithium cobalt oxide material, and a lithium manganese oxide material, wherein the chemical formula of the nickel cobalt manganese oxide material is LiNi x Co y Mn zO2, x+y+z=1, 0.33≤x≤0.9, y>0, z>0.

[0021] The implementation of the present invention has at least the following beneficial effects:

[0022] The preparation method of the lithium titanate negative electrode material provided by the present invention includes the steps of two spray dryings, two sinterings and the like, and the sintering temperature is limited to 400-600°C. This method can not only reduce the tightness of particle bonding and particle hardness, making it easier to compact, but also reduce the concentration of particle size distribution. During the compaction process, small particles can fill the gaps between large particles to achieve a tight arrangement, thereby improving the compaction density of the lithium titanate negative electrode material. The lithium titanate negative electrode material is applied to lithium-ion batteries, which helps to improve the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope (SEM) image of the lithium titanate negative electrode material in Example 1 of the present invention;

[0024] Figure 2 This is a SEM image of the negative electrode material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0026] As described in the background of the present invention, the prior art has a problem that the compaction density of lithium titanate negative electrode materials is low, resulting in a low energy density of lithium titanate batteries. In order to solve the above problem, the first aspect of the present invention provides a method for preparing a lithium titanate negative electrode material, comprising the following steps:

[0027] Step S1, mixing a lithium source, a titanium source and a first solvent, and performing a first ball milling process to obtain a first slurry;

[0028] Step S2, subjecting the first slurry to a first spray drying process to obtain a first precursor;

[0029] Step S3, performing a first sintering treatment on the first precursor to obtain an intermediate product;

[0030] Step S4, mixing the intermediate product with a second solvent, and performing a second ball milling process to obtain a second slurry;

[0031] Step S5, subjecting the second slurry to a second spray drying process to obtain a second precursor;

[0032] Step S6, performing a second sintering treatment on the second precursor to obtain a lithium titanate negative electrode material;

[0033] The temperatures of the first sintering treatment and the second sintering treatment are independently 400 to 600°C.

[0034] Specifically, in step S1, a lithium source and a titanium source are mixed with a first solvent, and a first dispersion is formed after a first stirring and dispersion, and then the first dispersion is subjected to a first ball milling treatment to obtain a first slurry. The rotation speed of the first stirring and dispersion is 1000-3000 r / min, and the time is 2-4 hours. In step S2, the first slurry is subjected to a first spray drying treatment to remove moisture and form spherical particles, i.e., a first precursor. In step S3, the first precursor is subjected to a first sintering treatment to obtain spherical primary particles, i.e., an intermediate product. In step S4, the intermediate product is mixed with a second solvent, and a second dispersion is formed after a second stirring and dispersion, and then the second dispersion is subjected to a second ball milling treatment to obtain a second slurry. The rotation speed of the second stirring and dispersion is 1000-3000 r / min, and the time is 2-4 hours. In step S5, the second slurry is subjected to a second spray drying treatment to remove moisture and form spherical particles, i.e., a second precursor. Step S6, performing a second sintering treatment on the second precursor to obtain spherical secondary particles, namely, lithium titanate negative electrode material.

[0035] The temperature of the first sintering treatment is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C or any two thereof, and the temperature of the second sintering treatment is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C or any two thereof. By coordinating the steps and limiting the temperatures of the first sintering treatment and the second sintering treatment to the above range, the sintering temperature is lower than that in the prior art, which is conducive to obtaining spherical or quasi-spherical secondary particles formed by mixing large and small particles, making the particle size distribution wider, and reducing the bonding tightness between particles and the particle hardness, and coating it on the negative electrode current collector, it can achieve a close arrangement on the negative electrode sheet, thereby improving the compaction density of the battery.

[0036] According to the research of the present invention, the lithium titanate negative electrode material prepared by the above method has a higher compaction density. Applying it to the battery can significantly improve the energy density of the battery. This is because the preparation method of the lithium titanate negative electrode material provided by the present invention, through two spray drying, two sintering and other steps, and limiting the sintering temperature to 400-600 ° C, can not only reduce the tightness of particle bonding and particle hardness, making it easier to compact, but also reduce the concentration of particle size distribution. During the compaction process, small particles can fill the gaps between large particles to achieve a tight arrangement, thereby improving the compaction density of the lithium titanate negative electrode material. The lithium titanate negative electrode material is applied to lithium-ion batteries, which helps to improve the energy density of the battery.

[0037] In some embodiments, the D50 particle size of the intermediate product is 200 nm to 1 μm. By limiting the D50 particle size of the intermediate product, it is helpful to obtain a lithium titanate negative electrode material of a specific size and optimize the performance of the lithium titanate negative electrode material.

[0038] By adjusting the amount of lithium source and titanium source added, the lithium element and titanium element in the first slurry can meet the requirements of the stoichiometric ratio, thereby obtaining a lithium titanate negative electrode material with a specific stoichiometric ratio. In some embodiments, the molar ratio of lithium element to titanium element in the first slurry is 1:(1.20-1.25), for example, 1:1.20, 1:1.22, 1:1.23, 1:1.24, 1:1.25 or a range of any two of them. This helps to obtain a lithium titanate negative electrode material that meets the chemical formula Li4Ti5O 12 of lithium titanate material.

[0039] In some embodiments, the rotation speed of the first ball milling treatment is 3000-4000 r / min, for example, 3000 r / min, 3500 r / min, 4000 r / min or a range consisting of any two thereof, and the time is 1-3 h, for example, 1 h, 2 h, 3 h or a range consisting of any two thereof; and / or, the rotation speed of the second ball milling treatment is 3000-4000 r / min, for example, 3000 r / min, 3500 r / min, 4000 r / min or a range consisting of any two thereof, and the time is 1-3 h, for example, 1 h, 2 h, 3 h or a range consisting of any two thereof.

[0040] In some embodiments, the temperature of the first spray drying process is 100-220°C, for example, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C or any two thereof, and the spray flow rate is 5-10m 3 / h, for example 5m 3 / h、6m 3 / h、7m 3 / h、8m 3 / h、9m 3 / h、10m 3 / h or any two thereof; and / or, the temperature of the second spray drying process is 100-220°C, for example, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C or any two thereof, and the spray flow rate is 5-10m 3 / h, for example 5m 3 / h、6m 3 / h、7m 3 / h、8m 3 / h、9m 3 / h、10m 3 / h or any combination of the two. By controlling the spray flow rate within the above range, it can be ensured that the material is evenly distributed during the drying process, thereby improving the drying efficiency and product quality.

[0041] The temperature of the first sintering treatment is 400-600°C, the time is 1-3h, for example, 1h, 2h, 3h or a range consisting of any two thereof, and the heating rate is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min; and / or, the temperature of the second sintering treatment is 400-600°C, the time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h, 6h or a range consisting of any two thereof, and the heating rate is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min. By limiting the heating rate to the above range, overburning of the material caused by too fast a heating rate can be avoided.

[0042] In some embodiments, the solid-liquid ratio in the first slurry is 10% to 30%; and / or, the solid-liquid ratio in the second slurry is 40% to 80%. The solid-liquid ratio refers to the ratio of solid matter to liquid matter in the slurry. By limiting the solid-liquid ratio to the above range, it helps to improve the ball milling efficiency.

[0043] In some embodiments, the lithium source includes at least one of lithium carbonate and lithium hydroxide; the titanium source includes at least one of titanium dioxide and metatitanic acid; and / or the first solvent and the second solvent are each independently selected from water.

[0044] After the second sintering treatment, the product of the second sintering treatment is cooled, and then sieved and demagnetized to finally obtain a lithium titanate negative electrode material.

[0045] The second aspect of the present invention provides a lithium titanate negative electrode material, which is prepared by the preparation method provided by the first aspect.

[0046] Since the lithium titanate negative electrode material is prepared by the above-mentioned specific preparation method, it has a relatively high compaction density, and its application in lithium-ion batteries helps to improve the energy density of the batteries.

[0047] In some embodiments, the lithium titanate negative electrode material is a secondary particle structure, and the secondary particles are composed of primary particles. Specifically, the lithium titanate negative electrode material is composed of a plurality of secondary particles, and the secondary particles have a spherical or quasi-spherical structure. The secondary particles can be porous secondary particles formed by agglomeration of primary particles.

[0048] In some embodiments, the particle size distribution width of the lithium titanate negative electrode material is 2.5 to 2.8. By limiting the particle size distribution width SPAN of the lithium titanate negative electrode material within an appropriate range, the particle size distribution width is made more dispersed, which is beneficial to improving the compaction density of the lithium titanate negative electrode material and can provide a certain mechanical strength and a higher energy density.

[0049] Specifically, the particle size distribution width of the lithium titanate negative electrode material substantially refers to the particle size distribution width of all secondary particles in the lithium titanate negative electrode material. The particle size distribution width of the lithium titanate negative electrode material is calculated according to the formula (D90-D10) / D50, where D10 is the particle size corresponding to 10% of the volume cumulative distribution percentage of the sample, D50 is the particle size corresponding to 50% of the volume cumulative distribution percentage of the sample, and D90 is the particle size corresponding to 90% of the volume cumulative distribution percentage of the sample.

[0050] The present invention does not limit the test method of D10, D50, and D90 of the lithium titanate negative electrode material. For example, a laser particle size analyzer may be used for measurement.

[0051] The present invention does not limit the specific values ​​of D10, D50, and D90. For example, in some embodiments, the D50 particle size of the lithium titanate negative electrode material is 5 to 15 μm, D10 is 0.5 to 4 μm, and D90 is 16 to 20 μm. By limiting the particle size to meet the above requirements, the particle size distribution width of the lithium titanate negative electrode material can be achieved to be 2.5 to 2.8, thereby improving the mechanical strength and compaction density, and preventing the lithium titanate negative electrode material from cracking during stress and circulation.

[0052] In some embodiments, the specific surface area of ​​the lithium titanate negative electrode material is 5 to 6 m 2 By limiting the specific surface area of ​​the lithium titanate negative electrode material within the above range, the specific surface area of ​​the negative electrode material is increased, so that the active sites participating in the electrochemical reaction are increased, which helps to improve the energy density and lithium ion transmission efficiency, thereby helping to improve the specific capacity and rate performance of the battery formed by the negative electrode material.

[0053] In some embodiments, the tap density of the lithium titanate negative electrode material is 1.0 to 1.2 g / cm3 , where tap density refers to the mass per unit volume of the powder in the container after being tapped under specified conditions. By limiting the tap density of the lithium titanate negative electrode material to the above range, it is possible to further ensure the compaction density when forming the positive electrode sheet, thereby helping to improve the energy density of the battery.

[0054] In some embodiments, the compaction density of the lithium titanate negative electrode material is 2 to 2.5 g / cm 3 By limiting the compaction density of the lithium titanate negative electrode material to the above range, the energy density of the battery assembled therefrom can be significantly improved, and cracking can be avoided during stress and cycling.

[0055] The third aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator; wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and the material of the negative electrode active material layer comprises the lithium titanate negative electrode material provided in the second aspect.

[0056] Due to the inclusion of the above-mentioned specific lithium titanate negative electrode material, the lithium ion battery has excellent energy density.

[0057] Specifically, the material of the negative electrode active material layer further includes a conductive agent and a binder. The conductive agent may be carbon black, and the binder may be polyvinylidene fluoride.

[0058] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the material of the positive electrode active material layer comprises one of a nickel cobalt manganese oxide material, a lithium cobalt oxide material, and a lithium manganese oxide material, wherein the chemical formula of the nickel cobalt manganese oxide material is LiNi x Co y Mn z O2, x+y+z=1, 0.33≤x≤0.9, y>0, z>0.

[0059] The separator includes a polyolefin film substrate and a ceramic coating coated on one side of the polyolefin film substrate. In the specific implementation of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet can be stacked in order, and then the electrolyte is injected to obtain a lithium-ion battery, and the ceramic coating is arranged adjacent to the positive electrode sheet.

[0060] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0061] Example 1

[0062] The method for preparing the lithium titanate negative electrode material of this embodiment comprises the following steps:

[0063] Step S1, weigh Li2CO3 and TiO2 at a molar ratio of lithium to titanium of 1:1.25, add them into a container filled with deionized water, stir and disperse them, and then add them into a ball mill filled with grinding balls for ball milling to obtain a first slurry; the stirring speed is 2000r / min, and the stirring time is 3h; the speed of the ball mill is 3000r / min, and the ball milling time is 1h; the solid-liquid ratio in the first slurry is 30%;

[0064] Step S2, subjecting the first slurry to a first spray drying process to obtain a first precursor; the temperature of the first spray drying process is 200°C, and the spray flow rate during the spray drying process is 8m 3 / h;

[0065] Step S3, subjecting the first precursor to a first sintering treatment to obtain an intermediate product; the first sintering treatment is performed at a temperature of 600° C., a time of 2 h, and a heating rate of 3° C. / min;

[0066] Step S4, mixing the intermediate product with water, and then adding it into a ball mill containing grinding balls for ball milling to obtain a second slurry; the stirring speed is 2000r / min, and the stirring time is 3h; the speed of the ball mill is 3000r / min, and the ball milling time is 1h; the solid-liquid ratio in the second slurry is 50%;

[0067] Step S5, subjecting the second slurry to a second spray drying process to obtain a second precursor; the temperature of the second spray drying process is 200°C, and the spray flow rate during the spray drying process is 8m 3 / h;

[0068] Step S6, subjecting the second precursor to a second sintering treatment, and after the product is cooled, screening and demagnetization are performed to obtain a lithium titanate negative electrode material; the temperature of the second sintering treatment is 600°C, the time is 2h, and the heating rate is 3°C / min.

[0069] Example 2

[0070] The difference from Example 1 is that in step S3, the temperature of the first sintering treatment is 400° C. and the time is 4 hours; in step S6, the temperature of the second sintering treatment is 400° C. and the time is 4 hours.

[0071] Example 3

[0072] The difference from Example 1 is that in step S3, the temperature of the first sintering treatment is 500° C. and the time is 3 hours; in step S6, the temperature of the second sintering treatment is 500° C. and the time is 3 hours.

[0073] Example 4

[0074] The difference from Example 1 is that, in step S1, LiOH and metatitanic acid are weighed at a molar ratio of lithium element to titanium element of 1:1.25.

[0075] Example 5

[0076] The difference from Example 1 is that in step S1, the rotation speed of the first ball milling treatment is 4000 r / min and the time is 1 hour; in step S4, the rotation speed of the second ball milling treatment is 4000 r / min and the time is 1 hour.

[0077] Example 6

[0078] The difference from Example 1 is that in step S1, the rotation speed of the first ball milling treatment is 6000 r / min and the time is 1 hour; in step S4, the rotation speed of the second ball milling treatment is 6000 r / min and the time is 1 hour.

[0079] Example 7

[0080] The difference from Example 1 is that in step S2, the temperature of the first spray drying process is 100°C and the spray flow rate is 5m 3 / h; in step S5, the temperature of the second spray drying process is 100°C and the spray flow rate is 5m 3 / h.

[0081] Example 8

[0082] The difference from Example 1 is that in step S2, the temperature of the first spray drying process is 220°C and the spray flow rate is 10m 3 / h; in step S5, the temperature of the second spray drying treatment is 220°C and the spray flow rate is 10m 3 / h.

[0083] Example 9

[0084] The difference from Example 1 is that in step S2, the temperature of the first spray drying process is 90°C and the spray flow rate is 5m 3 / h; in step S5, the temperature of the second spray drying treatment is 90°C and the spray flow rate is 5m 3 / h.

[0085] Comparative Example 1

[0086] The difference from Example 1 is that in step S3, the temperature of the first sintering treatment is 700°C, the time is 4 hours, and the heating rate is 8°C / min; in step S6, the temperature of the second sintering treatment is 700°C, the time is 8 hours, and the heating rate is 8°C / min.

[0087] Comparative Example 2

[0088] The preparation method of the lithium titanate negative electrode material of this comparative example comprises the following steps:

[0089] Step S1, adding Li2CO3 and TiO2 in a molar ratio of 1:1.25 into a container filled with deionized water, stirring and dispersing, and then adding into a ball mill filled with grinding balls for ball milling to obtain a slurry; the stirring speed is 2000r / min, and the stirring time is 3h; the speed of the ball mill is 3000r / min, and the ball milling time is 1h; the solid-liquid ratio in the slurry is 25%;

[0090] Step S2, spray drying the slurry to obtain a precursor; the spray drying temperature is 90°C, and the spray flow rate during the spray drying process is 8m 3 / h;

[0091] Step S3, sintering the precursor, and after the product is cooled, screening and demagnetization are performed to obtain a lithium titanate negative electrode material; the sintering temperature is 800°C, the time is 6h, and the heating rate is 5°C / min.

[0092] Comparative Example 3

[0093] The preparation method of the lithium titanate negative electrode material of this comparative example comprises the following steps:

[0094] Step S1, adding Li2CO3 and TiO2 in a molar ratio of 1:1.25 into a container filled with deionized water, stirring and dispersing, and then adding into a ball mill filled with grinding balls for ball milling to obtain a slurry; the stirring speed is 2000r / min, the stirring time is 3h; the speed of the ball mill is 3000r / min, the ball milling time is 1h; the solid-liquid ratio in the slurry is 20%;

[0095] Step S2, spray drying the slurry to obtain a precursor; the spray drying temperature is 90°C, and the spray flow rate during the spray drying process is 8m 3 / h;

[0096] Step S3, subjecting the precursor to two-stage sintering treatment, and after the product is cooled, screening and demagnetization are performed to obtain lithium titanate negative electrode material; the temperature of the first stage sintering treatment in the two-stage sintering treatment is 400°C, the time is 3h, and the heating rate is 5°C / min, and the temperature of the second stage sintering treatment is 800°C, the time is 6h, and the heating rate is 5°C / min.

[0097] Test example

[0098] 1. Tests of particle size, BET specific surface area, tap density and compacted density

[0099] Particle size: D50, D90, and D10 are obtained by testing with a laser particle size analyzer, and the particle size distribution width is calculated based on (D90-D10) / D50;

[0100] BET specific surface area: Use a specific surface area tester to test the specific surface area of ​​the powder.

[0101] Tap density: Use a tap density tester to test the tap density of powder.

[0102] Compaction density: Use roller press to test the compaction density of pole pieces.

[0103] 2. Test of electrochemical performance

[0104] 1. Battery assembly

[0105] Mixing lithium titanate material, carbon black SP, and polyvinylidene fluoride PVDF in a mass ratio of 94:2.5:3.5, adding N-methylpyrrolidone NMP to form a negative electrode slurry; coating the negative electrode slurry on the negative electrode current collector, rolling and drying to obtain a negative electrode sheet;

[0106] Mixing lithium nickel cobalt manganese oxide material, carbon black SP, and polyvinylidene fluoride PVDF in a mass ratio of 94:3:3, adding N-methylpyrrolidone NMP to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode current collector, rolling and drying to obtain a positive electrode sheet;

[0107] The positive electrode sheet, the separator and the negative electrode sheet are assembled into a battery, and an electrolyte is injected to obtain a battery; wherein the separator includes a polyolefin separator substrate and a ceramic coating coated on one side of the polyolefin separator substrate, the ceramic coating is arranged adjacent to the positive electrode sheet, the electrolyte is a lithium hexafluorophosphate solution with a mass concentration of 18%, and the solvent is an ethylene-carbonate copolymer EMC:ethylene carbonate EC with a mass ratio of 7:1.

[0108] 2. Specific capacity (mAh / g)

[0109] Use a battery charge and discharge tester to charge the battery to 2.5V at 1C constant current at 25°C, then charge it at constant voltage until the current drops to 0.02C. After standing for 5 minutes, discharge the battery to 1.3V at 1C constant current, and record the battery's discharge specific capacity Q. 1C .

[0110] 3. Battery energy density (Wh / kg)

[0111] Use a battery charge and discharge tester to charge the battery to 2.9V at 0.5C constant current at 25°C, then charge it at constant voltage until the current drops to 0.02C. After standing for 5 minutes, discharge the battery to 1.5V at 0.5C constant current, and record the battery's first discharge capacity Q 放and the first discharge energy E 放 , weigh the battery mass as W, and calculate the mass energy density ED = E 放 / W.

[0112] The test results are shown in Table 1.

[0113] Table 1

[0114]

[0115] Figure 1 This is a SEM image of the lithium titanate negative electrode material in the embodiment of the present invention. Figure 2 is a SEM image of the negative electrode material in the comparative example of the present invention, according to Figure 1 , Figure 2 As shown in Table 1, the particle size distribution width of the lithium titanate negative electrode material prepared by the preparation method of the embodiment is wide, and it has a high compaction density. Its application in lithium-ion batteries helps to improve the energy density and specific capacity of the battery. However, the lithium titanate negative electrode material prepared in Comparative Example 1 is a spherical secondary particle, the particle size distribution of the particles is relatively concentrated, and the particle hardness is large, resulting in a low compaction density of the negative electrode sheet, and the energy density and specific capacity of the battery are limited.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium titanate negative electrode material, characterized in that: The following steps are involved: Step S1, mixing a lithium source, a titanium source and a first solvent, and performing a first ball milling process to obtain a first slurry; Step S2, subjecting the first slurry to a first spray drying process to obtain a first precursor; Step S3, performing a first sintering treatment on the first precursor to obtain an intermediate product; Step S4, mixing the intermediate product with a second solvent, and performing a second ball milling process to obtain a second slurry; Step S5, subjecting the second slurry to a second spray drying process to obtain a second precursor; Step S6, performing a second sintering treatment on the second precursor to obtain a lithium titanate negative electrode material; Wherein, the temperatures of the first sintering treatment and the second sintering treatment are independently 400-600°C.

2. The preparation method according to claim 1, characterized in that: The D50 particle size of the intermediate product is 200 nm to 1 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The first ball milling treatment is performed at a rotation speed of 3000-4000 r / min for 1-3 h; and / or the second ball milling treatment is performed at a rotation speed of 3000-4000 r / min for 1-3 h.

4. The preparation method according to claim 1 or 2, characterized in that: The temperature of the first spray drying process is 100-220°C, and the spray flow rate is 5-10m 3 / h; and / or, the temperature of the second spray drying treatment is 100 to 220°C, and the spray flow rate is 5 to 10m 3 / h.

5. The preparation method according to claim 1 or 2, characterized in that: The first sintering treatment takes 1 to 3 hours, and the heating rate is 1 to 5°C / min; and / or the second sintering treatment takes 1 to 6 hours, and the heating rate is 1 to 5°C / min.

6. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of lithium element to titanium element in the first slurry is 1:(1.20-1.25); and / or, the lithium source includes at least one of lithium carbonate and lithium hydroxide; the titanium source includes at least one of titanium dioxide and metatitanic acid; and / or, the first solvent and the second solvent are each independently selected from water; and / or, the solid-liquid ratio in the first slurry is 10%-30%; and / or, the solid-liquid ratio in the second slurry is 40%-80%.

7. A lithium titanate negative electrode material, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. The lithium titanate negative electrode material according to claim 7, characterized in that: The lithium titanate negative electrode material is a secondary particle structure, and the secondary particles are composed of primary particles; the D50 particle size of the lithium titanate negative electrode material is 5 to 15 μm, the particle size distribution width is 2.5 to 2.8, and the specific surface area is 5 to 6 m 2 / g, tap density is 1.0~1.2g / cm 3 , compacted density is 2.0~2.5g / cm 3 .

9. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator; wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and the material of the negative electrode active material layer comprises the lithium titanate negative electrode material according to claim 7 or 8.

10. The lithium ion battery according to claim 9, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the material of the positive electrode active material layer includes one of a nickel cobalt manganese oxide material, a lithium cobalt oxide material, and a lithium manganese oxide material, wherein the chemical formula of the nickel cobalt manganese oxide material is LiNi x Co y Mn z O2,x+y+z=1.0.33≤x≤0.9,y=0.z=0。